Metastatic pericardial mass and cardiophrenic lymph nodes resection in ovarian cancer - Lingling Xie; Shaodan Lin; Haibo Zhao; Zhongqiu Lin; Huaiwu Lu (Elsevier, 2024)
Introduction: Epithelial Ovarian cancer most commonly presents at advanced stages with extra-abdominal disease metastasis. Notably, enlarged cardiophrenic lymph nodes are found in 10.5-62 % of patients with advanced ovarian cancer. However, the safety and feasibility of cardiophrenic lymph nodes dissection as a component of debulking surgery remains controversial (Acs et al., 2022; Agusti et al., 2024). Case/methods: We present a surgical video demonstrating the technique of bulky pericardial mass and metastatic cardiophrenic lymph nodes resection by transdiaphragmatic approach in advanced ovarian cancer. After the complete excision of intra-abdominal disease at laparotomy, the diaphragm is exposed, following the liver mobilization. According to the preoperative radiological examinations, the pericardial mass in the diaphragmatic space is reconfirmed, and then carefully removed by blunt and sharp dissection. Next, the pericardial cavity is closed by continuous suture. Through the transdiaphragmatic access to thoracic cavity, the pericardial fat pad containing cardiophrenic lymph nodes is explored and completely resected in view throughout. The diaphragm incision is closed continuously using non-absorbable suture with a biofilm, meanwhile, performing air aspiration in thoracic cavity. Conclusion: We demonstrate that advanced ovarian cancer with extra-abdominal diseases, such as bulky pericardial mass and cardiophrenic lymph nodes, should not be an absolute contraindication to a planned complete debulking surgery. Based on our growing experience, transdiaphragmatic approach is a safe and feasible access for metastatic cardiophrenic lymph nodes dissection.